Depressive symptoms are specifically related to speech pauses in schizophrenia spectrum disorders. (March 2023) - Tan, Eric J.; Neill, Erica; Kleiner, Jacqui L.; Rossell, Susan L.
Highlights: Speech pauses are related to depression, even in other psychiatric conditions. Both number and duration of pauses are related to depression. Speech pauses can be an objective quantitative depression assessment tool. Quantitative speech assessment is a promising assessment tool in psychiatry. Abstract: Depression is a common and debilitating mental illness associated with sadness and negativity and is often comorbid with other psychiatric conditions, such as schizophrenia. Depressive symptoms are presently primarily assessed through clinical interviews, however there are other behavioural indicators being investigated as more objective methods of depressive symptom assessment. The present study aimed to evaluate the utility of assessing depression using quantitative speech parameters by comparing speech between 23 schizophrenia/schizoaffective patients with clinically significant depressive symptoms (DP) 19 schizophrenia/schizoaffective patients without depressive symptoms (NDP) and 22 healthy controls with no psychiatric history (HC). Participant audio recordings were transcribed and analyzed to extract five types of speech variables: utterances, words, speaking rate, formulation errors and pauses. The results indicated that DP patients produced significantly more pauses within utterances, and had more utterances with pauses compared to NDP patients and HCs ( p  = <.05), who performed similarly to each other. Word, speaking rate and formulation errors variables were not significantly different between the patient groups ( p  > .05). The findings suggest that depressive symptoms may have a specific relationship to speech pauses, and support the potential future use of speech pause assessments as an alternative and objective depression rating and monitoring tool.